Acupotomy versus acupuncture for cervical spondylotic radiculopathy: protocol of a systematic review and meta-analysis. Issue 8 (8th August 2019) - Chen, Bin; Zhang, Cai; Zhang, Ren-Pan; Lin, An-Yang; Xiu, Zhong-Biao; Liu, Jing; Zhao, Hong-Jia
Abstract : Introduction: Cervical spondylotic radiculopathy (CSR) is the most common pattern of cervical spondylosis, which is a serious and common degenerative disease. Both acupotomy and acupuncture have been widely used clinically to treat CSR in China with satisfied efficacy. However, there is no systematic review comparing the effectiveness of these two therapies. The aim of this study is to compare the therapeutic efficacy and safety between acupotomy and acupuncture for patients with CSR to provide evidence for clinical practice. Methods and analysis: The following electronic databases will be searched: Web of Science, PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, China Biology Medicine disc, Wanfang Database and Chinese Scientific Journal Database (VIP). The randomised controlled trials of acupotomy versus acupuncture with/without additional treatment for CSR will be searched in the databases from their inception to December 2018 by two researchers independently. Visual analogue scale, symptom score and neck disability index will be assessed as the primary outcomes. The total effective rate, curative rate, adverse events and amount of rescue medication used will be assessed as the secondary outcomes. The Review Manager 5.3 will be used for meta-analysis and the evidence level will be assessed by using the method for Grading of Recommendations Assessment, Development and Evaluation. Continuous outcomes will be presented as the weighted mean difference or standardised mean difference with 95% CI, whereas dichotomous data will be expressed as relative risk with 95% CI. If the included studies have existing heterogeneity (p<0.05), then a random-effects model will be used. Otherwise, we will calculate using a fixed-effects model. Ethics and dissemination: Ethical approval is not required because no primary data are collected. This review will be published in a peer-reviewed journal and will be presented at an international academic conference for dissemination. PROSPERO registration number: CRD42019117348.